Análise da eficiência na educação dos municípios paulistas entre 2017 e 2021: uma abordagem não paramétrica - Silva, Aron Momberg da (Universidade Federal de São Carlos, 2026)
The present study evaluated the efficiency in the management of resources allocated to basic education in municipalities within the state of São Paulo, addressing the problem of allocative inefficiency where increases in per-pupil spending do not necessarily reflect improvements in educational indicators. To this end, Data Envelopment Analysis (DEA) was employed using the BCC model with variable returns to scale, alongside the inverted frontier method and a composite index to ensure a precise differentiation of all analyzed municipalities between 2017 and 2021. By modeling the relationship between socioeconomic and financial inputs relative to IDEB performance, the study sought to investigate the influence of population size and the adaptability of school networks in the face of exogenous shocks, such as the Covid-19 pandemic, providing evidence on the importance of technical management over budgetary expansion.
Efficiency analysis in education across São Paulo municipalities between 2017 and 2021: a non-parametric approach
Keywords: DEA; Eficiência; IDEB; Gasto Público; Efficiency; Public Expenditure; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA; 4. Educação de Qualidade